Computed Critiquing Integrated into Daily Clinical Practice Affects Physicians’ Behavior - Kuilboer, M. M.; van Wijk, M. A. M.; Mosseveld, M.; van der Does, E.; de Jongste, J. C.; Overbeek, S. E.; Ponsioen, B.; van der Lei, J. (Methods of Information in Medicine, 2006)
Objective: We developed AsthmaCritic, a non-inquisitive critiquing system integrated with the general practitioners’ electronic medical records. The system is based on the guidelines for asthma and chronic obstructive pulmonary disease (COPD) as issued by the Dutch College of General Practitioners. This paper assesses the effect of AsthmaCritic on monitoring and treatment of asthma and COPD by Dutch general practitioners in daily practice.Methods: A randomized clinical trial in 32 practices (40 Dutch general practitioners) using electronic patient records. An intervention group was given the use of AsthmaCritic, a control group continued working in the usual manner. Both groups had the disposal of the asthma and COPD guidelines routinely distributed by the Dutch College of General Practitioners. We measured the average number of contacts, FEV1 (forced ex-piratory volume), and peak-flow measurements per asthma/COPD patient per practice; and, the average number of antihistamine, cromoglycate, deptropine, and oral bronchodilator prescriptions per asthma/COPD patient per practice.Results: The number of contacts increased in the age group of 12-39 years. The number of FEV1, peak-flow measurements, and the ratio of coded measurements increased, whereas the number of cromoglycate prescriptions decreased in the age group of 12-39 years.Conclusions: Our study shows that the guideline-based critiquing system AsthmaCritic changed the manner in which the physicians monitored their patients and, to a lesser extent, their treatment behavior. In addition, the physicians changed their data-recording habits.
Keywords: Clinical decision support systems; computerized medical record; medical informatics; practice guidelines; feedback; asthma; COPD